Chloride Balance in Freshwater System of a Highly Anthropized Subalpine Area: Load and Source Quantification Through a Watershed Approach. Issue 1 (24th January 2020) - Nava, V.; Patelli, M.; Bonomi, T.; Stefania, G. A.; Zanotti, C.; Fumagalli, L.; Soler, V.; Rotiroti, M.; Leoni, B.
Abstract: Recent studies have highlighted an increase of chloride in many lakes worldwide, with negative effects on chemical and physical properties of inland waters and freshwater biota. In this study, we assessed the long‐term trend (1993–2017) of chloride in Lake Iseo, located in the midlatitudes, and analyzed its relationship with discharge data of the inflows and hydrological and hydroclimatic changes. Additionally, we performed a specific annual survey, collecting water samples at a biweekly frequency in tributaries, calculating chloride load, and comparing the result with the chloride increase observed in lacustrine water. The combined use of Geographic Information System (GIS) and multivariate analyses allowed identification of possible sources of chloride and their seasonal dynamic within the mixed‐land‐use watershed: impervious surface and deicing salt, population and sewage effluents, livestock, and rainwater. Their potential contribution to total mass balance was assessed, cross‐checking the results between chloride source evaluation and load estimation. Chloride load from wastewater treatment plants played an important role, albeit we highlighted that the main source was the road deicing salt, with a primarily winter contribution. The increased anthropization in the watershed was likely the main cause of the chloride enhancement. This study demonstrates that the problem of salinization can also affect lakes located in the midlatitude areas and provides a reproducible method for the identification and quantification of the different sources. Our results will help to better understand the potential sources of salinity in rivers that may reveal processes controlling the salinization of freshwater systems, with implications for future management practices. Key Points: A chloride increase was detected over 25 years in a lake of the midlatitudes, not related to the discharge of inflows The increased anthropization in the watershed is likely the main cause of the chloride increase in the lake Road deicing salt is the main source of chloride in the watershed, released only in the winter season